Home-Based Exercise Training in Childhood-Onset Takayasu Arteritis: A Multicenter, Randomized, Controlled Trial - Astley, Camilla; Clemente, Gleice; Terreri, Maria Teresa; Carneiro, Camila G.; Lima, Marcos S.; Buchpiguel, Carlos Alberto; Leão Filho, Hilton; de Sá Pinto, Ana Lúcia; Silva, Clovis Artur; Campos, Lucia Maria Arruda; Aikawa, Nadia Emi; Gil, Saulo; et al. (Frontiers in Immunology, 2021)
Introduction Childhood-onset Takayasu Arteritis (c-TA) is a rare, large-vessel vasculitis seen in children that could predisposing patients to a high risk of mortality. Exercise has the potential to improve overall health in several diseases, but evidence remains scant in c-TA. The main objective of this study was to investigate the safety and potential therapeutic effects of exercise in c-TA. Methods This was a 12-week, multicenter, randomized, controlled trial, to test the effects of a home-based, exercise intervention vs. standard of care in c-TA patients in remission. The primary outcomes were arterial inflammation, assessed by [18F] FDG- PET/MRI and systemic inflammatory markers. Secondary outcomes included, physical activity levels, functionality, body composition, disease-related parameters, and quality of life. Results Thirty-seven patients were assessed for eligibility, which represents the total number of c-TA patients being followed by the three specialized medical ambulatory services in Sao Paulo. After exclusions, fourteen c-TA patients (71.4% females) aged 12-25 years were randomly allocated into exercised (n=5) and non-exercised groups (n=9). Exercise did not exacerbate arterial inflammation. In fact, exercised patients had a reduction in the frequency of vessel segments with severe inflammation, whereas the non-exercised patients had an opposite response (P=0.007). Greater improvements in visceral fat, steps per day, functionality and physical component SF-36 were observed in the exercised patients (P ≤ 0.05). Conclusions Exercise is safe and may improve visceral fat, physical activity levels, functionality, and physical component SF-36 in c-TA patients. Thus, exercise arises as a novel, evidence-based intervention to improve general health in c-TA. Clinical Trial Registration https://www.clinicaltrials.gov/ct2/show/NCT03494062?term=NCT03494062&draw=2&rank=1, identifier NCT03494062.